Heritage regimes and the state - Peselmann, Arnika; Eggert, Aditya; Bendix, Regina 1958- (Universitätsverlag Göttingen, 2012)
What happens when UNESCO heritage conventions are ratified by a state? How do UNESCO's global efforts interact with preexisting local, regional and state efforts to conserve or promote culture? What new institutions emerge to address the mandate? The contributors to this volume focus on the work of translation and interpretation that ensues once heritage conventions are ratified and implemented. With seventeen case studies from Europe, Africa, the Caribbean and China, the volume provides comparative evidence for the divergent heritage regimes generated in states that differ in history and political organization. The cases illustrate how UNESCOś aspiration to honor and celebrate cultural diversity diversifies itself. The very effort to adopt a global heritage regime forces myriad adaptations to particular state and interstate modalities of building and managing heritage.
Keywords: UNESCO; state; heritage; regimes; cultural diversity; cultural property; History (General); Social sciences (General); Nationalstaat; Denkmalpflege; Kulturerbe; Welterbe; Aufsatzsammlung; Konferenzschrift